2020
DOI: 10.1021/acs.jpcc.9b11070
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Energetic Coordination Polymers Based on Functionalized GO and Their Catalytic Effects on the Decomposition of AP and RDX

Abstract: In this study, new highly energetic coordination polymers (ECPs) were successfully prepared by a facile chemical modification method based on functionalized graphene oxide (GO) sheets. Simple cross-linked GO layers with triaminoguanidine ligand (T) may further be bonded with crystals containing T and transition metal ions (T–M) using cobalt, zinc, silver, or iron as coordination centers, generating 2D-layered energetic hybrid ECPs crystals. Successful functionalization of the prepared ECPs was confirmed by SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…The spectra of CMS and Fe 2 O 3 -CMS displayed two characteristic bands. The first at 1357 cm −1 , assigned to the D band, is related to structural defects, whereas the second at 1574 cm −1 corresponded to the G band, representing the graphitic structure in carbon materials [ 38 , 59 ]. It has been reported that the D/G ratio of band intensities represents the graphitic structure with respect to the structure disorder [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of CMS and Fe 2 O 3 -CMS displayed two characteristic bands. The first at 1357 cm −1 , assigned to the D band, is related to structural defects, whereas the second at 1574 cm −1 corresponded to the G band, representing the graphitic structure in carbon materials [ 38 , 59 ]. It has been reported that the D/G ratio of band intensities represents the graphitic structure with respect to the structure disorder [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our research group designed GO-doped transition metal (Co) complexes of T and assessed their catalytic effect toward ammonium perchlorate, RDX, and NTO. 35,36 However, to the best knowledge of the authors, such type of catalysts has never been applied as additive of energetic co-crystals. Besides that, the use of GO as catalytic support may play a synergistic effect with the other ingredients, which will enhance the stability as well the decomposition efficient of the developed energetic co-crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This latter is also compared to the co-crystal of a molar ratio 1 : 1, developed in our recent work, 29 in terms of structure and thermal behavior in a detailed manner. Aer that, a deep investigation of the catalytic effect of the two high energetic 2D-catalysts, namely, T-Co and GO-T-Co-T, developed in our previous study, 35 on the thermolysis of HNTO/AN by means of nonisothermal differential scanning calorimetry (DSC). The kinetic parameters, including the energy of activation, preexponential factor and the reaction models of the co-crystal supplemented with catalysts have been calculated by means of four isoconversional integral methods, viz., Trache-Abdelaziz-Siwani (TAS), iterative Kissinger-Akahira-Sunose (it-KAS), iterative Flynn-Wall-Ozawa (it-FWO) and Sbirrazzuoli methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-based nanomaterials possess exceptional electrical, optical, mechanical, electrochemical and thermal features that make them versatile for a wide range of applications and have drawn worldwide attention in both academic and engineering fields [ 44 , 105 ]. They can be employed in industrial applications such as biomedical, solar cells, biosensors, supercapacitors, electromagnetic absorbers, optical devices, integrated circuit, protective coatings, organic light-emitting diodes, sound transducers, petroleum industry, automobile components, aerospace, energy storage, nanocomposites and contamination purification in wastewater management, to cite a few ( Figure 3 f) [ 107 , 115 , 116 ].…”
Section: Graphene-based Nanomaterialsmentioning
confidence: 99%